Myrsine guianensis Rapanca, Myrsine: FPS420/FP420, 6/2007 - Gilman, Edward (EDIS, 2007)
This document provides an overview of Myrsine guianensis, commonly known as Rapanca or Myrsine. It describes the plant’s physical characteristics, including its height, spread, and growth habit. The document highlights the plant’s adaptability to various soil types and environmental conditions, such as its tolerance to drought and salt spray. It also outlines the plant’s uses in landscaping, emphasizing its suitability for hedges, screens, and reclamation projects. Additionally, the document notes that Myrsine guianensis is an evergreen shrub that produces shiny black berries, which attract birds. Original publication date September 1999.